The Philosophy of Evidence-Based Medicine - Howick, J (Wiley-Blackwell, 2011)
Evidence-based medicine (EBM) has become a required element of clinical practice, but it is critical for the healthcare community to understand the ongoing controversy surrounding EBM. Seeking to address questions raised by critics, The Philosophy of Evidence-based Medicine challenges the over dependency of EBM on randomized controlled trials. This book also explores EBM methodology and its relationship with other approaches used in medicine. © 2011 Jeremy Howick.